Comment on the view of the Human Rights Committee in the case of Ioane Teitiota v. New Zealand - Stojanović, Bojan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The paper analyzes the findings of the Human Rights Committee in the case of Ioane Teitiota v. New Zealand. The procedure was conducted in accordance with the provisions of the International Covenant on Civil and Political Rights and the First Optional Protocol to the Covenant. The Committee considered the violation of the right to life contained in article 6, paragraph 1, of the Covenant. The applicant argued that his return to Kiribati, his country of origin, would jeopardize his right to life. The statement considered the negative effects of environmental damage and the impact of climate change on the applicant's right to life. The main hypothesis of the paper is to consider the Committee's statement in the light of expanding the protection of the right to life and paving the way for recognizing the impact of climate change based on human migration, which could develop normative activity and practice of international bodies and states in the direction of recognizing so-called environmental refugees.
Keywords: right to life; right to asylum; International Covenant on Civil and Political Rights; Human Rights Committee; environment; climate change; sea level rise; environmental refugees